2019
DOI: 10.1021/acs.jpca.9b04144
|View full text |Cite
|
Sign up to set email alerts
|

Potential Energy Surfaces of HN(CH)SX:CO2for X = F, Cl, NC, CN, CCH, and H: N···C Tetrel Bonds and O···S Chalcogen Bonds

Abstract: MP2/aug′-cc-pVTZ calculations have been performed in search of complexes, molecules, and transition structures on the HN­(CH)­SX:CO2 potential energy surfaces, for X = F, Cl, NC, CN, CCH, and H. Complexes stabilized by traditional N···C tetrel bonds and O···S chalcogen bonds exist on all surfaces and are bound relative to the isolated monomers. Molecules stabilized by an N–C covalent bond and an O···S chalcogen bond are found when X = F, Cl, and NC, but only the HN­(CH)­SF:CO2 molecule is bound. The binding en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The binding energies are refined further from the single point energy calculations at the MP2/aug-cc-pVTZ//MP2/aug-cc-pVDZ level. This method has been applied in several recent studies of noncovalent interaction and found to be quite reliable [46,[56][57][58]. The binding energy of the complexes was calculated using the usual super molecular approach where the energies of the optimized monomers are subtracted from the energy of the complex.…”
Section: Computational Methodologymentioning
confidence: 99%
“…The binding energies are refined further from the single point energy calculations at the MP2/aug-cc-pVTZ//MP2/aug-cc-pVDZ level. This method has been applied in several recent studies of noncovalent interaction and found to be quite reliable [46,[56][57][58]. The binding energy of the complexes was calculated using the usual super molecular approach where the energies of the optimized monomers are subtracted from the energy of the complex.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Since most molecules have several kinds of atoms, and since all atoms can be Lewis acids, then, confronted with a Lewis base, several types of NCIs can be formed. For this reason, many papers have been devoted to the competition between some combination of hydrogen, alkaline-earth, tetrel, pnictogen, chalcogen, and halogen bonds [157,[183][184][185][186][187][188][189][190]. Curiously, although the nature of the base can change the nature of the most stable acid, none of these publications reported an inversion of acidity.…”
Section: Chalcogen Bondsmentioning
confidence: 99%
“…Nor is there a limitation to planar geometries, as π-holes are also common in linear molecules, such as the area above the C atom of CO 2 [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ], OCS [ 49 , 50 , 51 ], N 2 O, and CS 2 [ 52 , 53 , 54 ]. Just as their σ-hole analogs facilitate attractions toward a nucleophile, the same is true of these π-holes.…”
Section: Introductionmentioning
confidence: 99%